Resistivity, ESR, and Radiation Shielding Properties of the Volcanic Rock Materials - Nuhoglu, Cigdem; Tapan, Mucip; Okutan, Mustafa; Aydin, Sureyya; Yalcin, Zeynel; Icelli, Orhan; Kavanoz, H. Birtan; Orak, Salim (HINDAWI LTD, 2014)
Pumices have been used in cement, concrete, brick, and ceramic industries as an additive and aggregate material. It will be important to study pumice types by using a different tool as EPR which is a new technique for related material to be used for industrial aims. Electron spin resonance (ESR) spectra of the pumice types were taken by EMX-type spectrometer. Also, the current-voltage (I-V) and surface resistivity probe stand of the thin films was studied using a four-point probe measurements. The relationship between radiation shielding properties of the pumice samples and their surface resistivity, chemical, and electrokinetic properties was evaluated using simple regression analysis. Simple regression analysis indicated a strong correlation between surface resistivity and density and SiO2, Fe2O3, CaO, MgO, and TiO2 content of pumice samples in this study. It is found that a correlation between determined g-factor by EPR spectroscopy and radiation shielding is established for pumice samples.
Keywords: PUMICE; Physics